A MECHANISM FOR PUMPING WATER INTO SMALL OIL FIELDS (American Journal of Technology and Applied Sciences, 2025)
Waterflooding was first applied in the Fergana oil fields in 1952, when pilot water injection was started into the peripheral part of the V+VI horizon reservoir of the Yuzhny Alamishik field. The positive effect of the pilot injection, expressed in a certain increase in the flow rate of wells in terms of oil and liquid, gave grounds to start industrial waterflooding of these horizons in 1953.In 1954, waterflooding was started along the VIII horizon of the Khojaabad field and the VII horizon of the Yuzhny Alamishik field.In the first years of the introduction of artificial waterflooding methods, the greatest preference was given to systems for injecting water into the peripheral parts of the reservoirs. However, the process of development and operation of these systems in Fergana faced serious difficulties, mainly due to the poor hydrodynamic connection between the peripheral and oil parts of the reservoir.